Timing of heart failure development and clinical outcomes in patients with acute myocardial infarction - Kim, Hyung Yoon; Kim, Kye Hun; Lee, Nuri; Park, Hyukjin; Cho, Jae Yeong; Yoon, Hyun Ju; Ahn, Youngkeun; Jeong, Myung Ho; Cho, Jeong Gwan (Frontiers in Cardiovascular Medicine, 2023)
Background and objectives To investigate the clinical relevance of the timing of heart failure (HF) development on long-term outcome in patients with acute myocardial infarction (AMI). Materials and methods A total of 1,925 consecutive AMI patients were divided into 4 groups according to the timing of HF development; HF at admission (group I, n = 627), de novo HF during hospitalization (group II, n = 162), de novo HF after discharge (group III, n = 98), no HF (group IV, n = 1,038). Major adverse cardiac events (MACE) defined as the development of death, re-hospitalization, recurrent MI or revascularization were evaluated. Results HF was developed in 887 patients (46.1%) after an index AMI. HF was most common at the time of admission for AMI, but the development of de novo HF during hospitalization or after discharge was not uncommon. MACE was developed in 619 out of 1,925 AMI patients (31.7%). MACE was highest in group I, lowest in group IV, and significantly different among groups; 275 out of 627 patients (43.9%) in group I, 64 out of 192 patients (39.5%) in group II, 36 out of 98 patients (36.7%) in group III, and 235 out of 1,038 patients (22.6%) in group IV (P < 0.001). MACE free survival rates at 3 years were 56% in group I, 62% in group II, 64% in group III, and 77% in group IV (P < 0.001). Conclusions HF was not uncommon and can develop at any time after an index AMI, and the development of HF was associated with poor prognosis. The earlier the HF has occurred after AMI, the poorer the clinical outcome was. To initiate the guideline directed optimal medical therapy, therefore, the development of HF should be carefully monitored even after the discharge from an index AMI.